Supporting small suppliers through buyer-backed purchase order financing. Issue 18 (17th September 2018) - Huang, Boray; Wu, Andy; Chiang, David
Abstract : This paper considers a creditworthy buyer who has two supplies: a low-cost but capital-constrained unreliable SME (small and medium-sized enterprise), and a high-cost but reliable backup source. The buyer may consider a novel financing mechanism named BPOF (buyer-backed purchase order financing) for supporting the SME indirectly. Under the BPOF scheme, the buyer provides partial or full guarantee to share the bank's financing risk thus facilitate the SME's loan application. To balance the risk with the benefit due to BPOF, we specify the conditions under which BPOF works and identify the properties of the buyer's optimal strategy for sourcing and guaranteeing jointly. Generally speaking, a rational buyer's guarantee should positively correlate to her product margins and the suppliers' reliability. Finally, we claim when the risk-adjusted wholesale price is sufficiently low, dual financing (BPOF and subsidy) should be suggested.